Role of genetics in infection-associated arthritis. Issue 2 (April 2015) - Benham, Helen; Robinson, Philip C.; Baillet, Athan C.; Rehaume, Linda M.; Thomas, Ranjeny
Abstract Genetic discoveries in arthritis and their associated biological pathways spanning the innate and adaptive immune system demonstrate the strong association between susceptibility to arthritis and control of exogenous organisms. The canonical theory of the aetiology of immune-mediated arthritis and other immune-mediated diseases is that the introduction of exogenous antigenic stimuli to a genetically susceptible host sets up the environment for an abnormal immune response manifesting as disease. A disruption in host-microbe homeostasis driven by disease-associated genetic variants could ultimately provide the source of exogenous antigen triggering disease development. We discuss genetic variants impacting the innate and adaptive arms of the immune system and their relationship to microbial control and arthritic disease. We go on to consider the evidence for a relationship between HLA-B27, infection and arthritis, and then emerging evidence for an interaction between microbiota and rheumatoid arthritis.